Energy intake and dietary fiber as principal determinants of obesity in Eastern Europe, 2010–2022: an ecological panel study - Siminiuc, Rodica; Țurcanu, Dinu; Siminiuc, Sergiu (Frontiers in Public Health, 2025)
BackgroundObesity is a major global health challenge, with Eastern Europe standing out for rapid nutrition transitions and persistent social and economic inequalities. Despite its high prevalence, longitudinal ecological evidence on the structural determinants of obesity in this region remains limited.ObjectiveTo examine population-level associations between dietary energy availability, dietary fiber intake, macronutrient composition, and insufficient physical activity with obesity and overweight prevalence in Eastern Europe during 2010–2022.MethodsData from FAOSTAT and the World Health Organization were assembled into a balanced panel of 130 country–year observations. Analyses combined descriptive statistics and Pearson correlations with two-way fixed-effects regressions (country and year), using robust standard errors and one-year lagged predictors to test for robustness.ResultsHigher energy availability was positively associated with both obesity and overweight, while dietary fiber consistently showed a protective effect. Marginal estimates indicated that an additional 100 kcal/day predicted an increase of nearly one percentage point in obesity, whereas +5 g/day of fiber corresponded to an approximate two-percentage-point reduction. Neither macronutrient shares nor insufficient physical activity showed significant associations.ConclusionDietary energy and fiber emerge as the primary structural correlates of obesity in Eastern Europe. These findings underscore the need for region-specific, data-driven nutrition and public health policies to address obesogenic environments and reduce socio-economic disparities in diet quality.